2019
DOI: 10.1128/msphere.00511-19
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Extracytoplasmic Function σ Factor σ P by β-Lactams in Bacillus thuringiensis Requires the Site-2 Protease RasP

Abstract: Bacteria can utilize alternative σ factors to regulate sets of genes in response to changes in the environment. The largest and most diverse group of alternative σ factors are the extracytoplasmic function (ECF) σ factors. σP is an ECF σ factor found in Bacillus anthracis, Bacillus cereus, and Bacillus thuringiensis. Previous work showed that σP is induced by ampicillin, a β-lactam antibiotic, and required for resistance to ampicillin. However, it was not known how activation of σP is controlled or what other … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(53 citation statements)
references
References 65 publications
6
47
0
Order By: Relevance
“…In Bacillus anthracis , Bacillus cereus , and Bacillus thuringiensis , resistance to penicillin and other β-lactam antibiotics is dependent upon σ P , an ECF σ factor ( 33 , 34 ). σ P was originally classified as a member of the ECF01 group of ECF σ factors but was recently reclassified to the ECF265 group, the members of which are primarily found in Firmicutes ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Bacillus anthracis , Bacillus cereus , and Bacillus thuringiensis , resistance to penicillin and other β-lactam antibiotics is dependent upon σ P , an ECF σ factor ( 33 , 34 ). σ P was originally classified as a member of the ECF01 group of ECF σ factors but was recently reclassified to the ECF265 group, the members of which are primarily found in Firmicutes ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of σ P results in the expression of at least two genes that encode β-lactamases and are involved in resistance to penicillin, ampicillin, and other β-lactam antibiotics. σ P also activates the expression of its operon, thus controlling the expression of sigP and rsiP ( 33 , 34 ). We previously demonstrated that σ P is activated in the presence of a subset of β-lactams, ampicillin, methicillin, cefoxitin, cephalothin, and cefmetazole, but not other cell envelope stresses ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations